Direct Splash Dispersal Prevails over Indirect and Subsequent Spread during Rains in Colletotrichum gloeosporioides Infecting Yams - Penet, Laurent (PLoS One, 2014)
Plant pathogens have evolved many dispersal mechanisms, using biotic or abiotic vectors or a combination of the two. Rain splash dispersal is known from a variety of fungi, and can be an efficient driver of crop epidemics, with infectious strains propagating rapidly among often genetically homogenous neighboring plants. Splashing is nevertheless a local dispersal process and spores taking the droplet ride seldom move farther than a few decimeters. In this study, we assessed rain splash dispersal of conidia of the yam anthracnose agent, Colletotrichum gloeosporioides, in an experimental setting using a rain simulator, with emphasis on the impact of soil contamination (i.e., effect of re-splashing events). Spores dispersed up to 50 cm from yam leaf inoculum sources, though with an exponential decrease with increasing distance. While few spores were dispersed via re-splash from spore-contaminated soil, the proportion deposited via this mechanism increased with increasing distance from the initial source. We found no soil contamination carryover from previous rains, suggesting that contamination via re-splashing from contaminated soils mainly occurred within single rains. We conclude that most dispersal occurs from direct splashing, with a weaker contribution of indirect dispersal via re-splash.